Efektivitas Penggunaan sistem informasi akuntansi SAP dalam program MBKM magang mandiri di PT Japfa Comfeed Indonesia Tbk Unit Gedangan - Moch Iqbal Romadhon (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study evaluates the effectiveness of the SAP accounting information system in supporting the implementation of the Independent Learning–Independent Campus (MBKM) Internship Program at PT Japfa Comfeed Indonesia Tbk, Gedangan Unit. SAP, as an integrated Enterprise Resource Planning (ERP) system, was adopted to replace the previous desktop-based system, which had significant limitations, such as restricted local access, dependence on additional licenses, and lower integration capabilities across departments. The main objective of this research is to determine how SAP contributes to improving organizational efficiency while simultaneously providing practical learning opportunities for students participating in the MBKM internship program. A descriptive qualitative approach was employed, with data collected through direct observation of company operations, semi-structured interviews with student interns and field supervisors, and analysis of company documentation. The findings indicate that the use of SAP has enhanced efficiency, accuracy, and speed in recording and reporting financial transactions. Through their internship, students engaged directly in business processes, particularly in handling purchase requisitions, reimbursement procedures, and asset management activities. This exposure enabled students to develop a deeper understanding of integrated financial systems and the workflow of a large-scale agribusiness corporation. Although several technical challenges were encountered, particularly in the form of temporary network disruptions, such issues did not substantially hinder the system’s overall performance. The availability of prompt technical support from the company’s IT team minimized potential negative impacts and ensured system continuity. Beyond improving corporate financial governance, SAP also offered valuable experiential learning for interns, bridging theoretical knowledge acquired in academic settings with real-world industrial applications. Overall, the study concludes that SAP functions not only as a strategic enterprise tool for the company but also as an effective educational medium that supports the success of the MBKM internship program.